Technical Study of the Great Mosque Interception - I Made Sukmayasa; Listralia Sinulingga (Pusat Penelitian dan Pengabdian Masyarakat Poltrada Bali, 2020)
Agung Mosque intersection in Kab. Karo has some very complicated problems. The high volume of traffic, canalization traffic flow is less than optimal, conflict high traffic and road facilities are inadequate and the need for management of traffic engineering by using the analysis based on the Transport Research Laboratory, which has been used by a few countries in the world , Then using these methods are proposed recommendations on the intersection of Agung Mosque Kab.Karo, such as widening the road, adding a traffic island, repair cycle time and green time between (Intergreen) adding facilities and infrastructure of the road. That way intersection performance can be increased so that the fluency and safety can be met.